Evelyn Hugo’s Defiance Against “True Womanhood” and Her Agency in The Seven Husbands of Evelyn Hugo - Florencia Elanie; Jenny Mochtar (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
In this study, we examine Taylor Jenkins Reid's historical fiction, The Seven Husbands of Evelyn Hugo (2017), focusing on how the protagonist, Evelyn Hugo, challenges the 1950s' values of True Womanhood. During this era, women were expected to be conventional housewives, but Evelyn, a young woman herself, rejects these traditional values, diverging from the ideal woman's life. This rebellion makes her character intriguing to study. My analysis explores how Evelyn defies the three virtues of True Womanhood and how this defiance grants her the agency to shape her own life. We will use Welter's 1966 critique, The Cult of True Womanhood, and Giddens' 1986 Concept of Agency to guide my analysis. The findings reveal that Evelyn defies societal norms by taking control of her body, rejecting societal expectations, and asserting her personal autonomy. Her desire for financial independence and self-reliance drives her defiance, allowing her to live without shame or guilt. Evelyn Hugo emerges as a feminist figure, using her defiance to gain agency in a male-dominated world and living ahead of her time.